Analysis of Sound Field Distribution in Architecturally Diverse Temples - BŁASZCZAK, Paweł; BERDOWSKA, Sylwia; BERDOWSKI, Janusz Marek (Archives of Acoustics, 2021)
The results of the research, which aimed to analyze the acoustic properties of selected sacred buildings located in the city of Czestochowa, Poland are presented in the paper. Three architecturally unusual and completely different from each other churches were selected for the study. The churches differed in shape of their buildings, cubic volume, years of construction, interior furnishings, etc. Nine different objective parameters were used to describe the physical properties of acoustical field in the studied churches. Various factors characterizing the acoustic properties of each building were determined, such as the distribution of sound pressure level (SPL), reverberation time T30, definition D50. Next, they were thoroughly analyzed, so as to ultimately obtain distributions of individual acoustic parameters in the space of the tested building. It allowed to evaluate the quality of the received verbal or musical message depending on the place where the listener was. Further research on speech intelligibility and the musical quality of churches was performed by determining the averaged values of next four objective acoustic parameters: centre time Ts, speech clarity C50, music clarity C80, and speech transmission index (STI). A new approach to analyzing the objective physical parameters describing the sound field was presented in Sec. 4. Mean free path length and critical distance were determined for the investigated acoustic fields in each church and they were associated with a general geometric factor characterizing the complexity of the room shape. The final part of the work presents a comparative analysis of the obtained results of acoustic quality tests of the temples, and thus their usefulness in terms achieving a maximum intelligibility of speech and music. The interesting similarities were found in the spatial distribution of individual acoustic parameters characterizing the distribution of the acoustic field in temples with completely different architecture.